Community-Based Intersectionality: The Changing Public Services Project - Findlay, Tammy; Cohen, Michelle; Johnston, Mary-Dan (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2019)
The paper reflects on a changing public service project regarding women and intersectional analysis in Halifax, Canada. The project sought to facilitate collective mobilizations to challenge austerity and to imagine public services that meet the needs of the citizens who use them, and the workers that provide them. We provide an overview of the project, and then explore our attempt at adapting “multistrand” intersectional policy analysis (Hankivsky & Cormier, 2011) to a community-based context. In considering the challenges and opportunities associated with this work, the paper concludes that the changing public service project created space for an innovative approach to community-based research that can guide both participatory policy analysis and collective action.